2021
DOI: 10.3390/diagnostics11060991
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Computerized Tomography-Based Radiomics for the Diagnosis of COVID-19 and Viral Pneumonia

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) led to a global pandemic. Although reverse transcription polymerase chain reaction (RT-PCR) of viral nucleic acid is the gold standard for COVID-19 diagnosis, its sensitivity was found to not be high enough in many reports. As radiomics-based diagnosis research has recently emerged, we aimed to use computerized tomography (CT)-based radiomics models to differentiate COVID-19 pneumonia from other viral pneumonia infections. Materials and methods: This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…To date, no systematic review or meta-analysis has been performed that includes all types of imaging techniques to diagnose COVID-19 and other pneumonias. Kao et al [51] evaluated the CT-based radiomics signature model to successfully distinguish COVID-19 from other viral pneumonias, and came to similar conclusions as ours, with high study heterogeneity. They assessed studies up to February 26, 2021, so only 6 studies were included, and all studies were conducted in China.…”
Section: Discussionsupporting
confidence: 74%
“…To date, no systematic review or meta-analysis has been performed that includes all types of imaging techniques to diagnose COVID-19 and other pneumonias. Kao et al [51] evaluated the CT-based radiomics signature model to successfully distinguish COVID-19 from other viral pneumonias, and came to similar conclusions as ours, with high study heterogeneity. They assessed studies up to February 26, 2021, so only 6 studies were included, and all studies were conducted in China.…”
Section: Discussionsupporting
confidence: 74%
“…Most of the radiomics studies were oncological, but radiomics has potential clinical application in the non-oncological field [ 30 ]. Several reviews have summarized the role of radiomics in non-oncological diseases, including mild cognitive impairment and Alzheimer’s disease [ 15 ], COVID-19 and viral pneumonia [ 16 ], and cardiac diseases [ 17 ]. The study quality evaluated by RQS was the main concern of these reviews.…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that the COVID-19 and viral pneumonia review reached a better RQS rating since the included studies were published recently with a relatively larger sample size, which allow adequate feature reduction and external validation. Actually, none of the studies in this review lacked the feature reduction, and all the studies performed validation [ 16 ]. In contrast, a significant number of previous studies did not perform feature reduction and validation.…”
Section: Discussionmentioning
confidence: 99%
“…The RQS values of the included literature ranged from seven to 16; thus, the highest RQS in the selected studies was only 40%. A previous meta-analysis also found a maximum RQS score of 16 for CT-based texture features used to differentiate between COVID-19 and viral pneumonia [ 14 ]. Compared with this study, a low RQS score makes it challenging to conduct a high-quality radiomics study in current research settings.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on COVID-19, machine learning CT-based radiomics has been shown to help diagnose and differentiate COVID-19 pneumonia from pneumonia caused by other pathogens [ 12 14 ]. Additionally, CT-based radiomics reportedly predicts the severity and outcome of COVID-19 pulmonary opacities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%